The second victims' experience and related factors among medical staff. Issue 3 (13th May 2019) - Mohamadi-Bolbanabad, Amjad; Moradi, Ghobad; Piroozi, Bakhtiar; Safari, Hossein; Asadi, Heshmatollah; Nasseri, Karim; Mohammadi, Hiwa; Afkhamzadeh, Abdorrahim
Abstract : Purpose: The purpose of this paper is to determine the second victims' experience and its related factors among medical staff. Design/methodology/approach: This research is a cross-sectional study that was conducted in public hospitals of Sanandaj, west of Iran, in 2017. The sample consisted of 338 medical staff including physicians, nurses and mid-wives. A self-report questionnaire was used for data collection. Descriptive statistics, cross-tabs and χ 2 test were used for data analysis using SPSS20. Findings: A total of 51.5 percent ( n =174) of the medical staff had experienced medical error in the past year, of which 90.2 percent ( n =157) had at least one of the symptoms of "second victims." Tachycardia and sleep disturbances were the most commonly referred physical symptoms with 73 and 51.7 percent, respectively. Also, repetitive/intrusive memories and fear of reputation damage were the most commonly referred psychosocial symptoms with 68.3 and 51.7 percent, respectively. The experience of physical and psychosocial symptoms was different according to the occupational category. In addition, there was a significant association between the experience of physical symptoms with the hospital administrators' awareness of medical errors and the consequences of medical errors for patients. Practical implications: Adoption of coping strategies, including learning from medical errors as well as hospital administrators' support from second victims, is recommended. It is also suggested that medical staff be informed about the consequences of medical errors as well as physical and psychological symptoms of second victims so that they can ask for help from managers and colleagues when the symptoms occur. Originality/value: This study outlines the prevalence, the most psychological and physical symptoms, and the demographic and occupational factors associated with the second victim phenomenon in medical staff. Also, the most important strategies for coping with this phenomenon are prioritized from the perspective of medical staff.